2018
DOI: 10.1002/slct.201801971
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Zr‐MTW Zeolites Doped with Copper as Catalysts of Ethanol Conversion into 1,3‐Butadiene

Abstract: The hierarchical Zr-MTW zeolites are prepared using NH 4 F and HF as mineralizing agents and structure-directed agent like Gemini-type surfactant and studied by X-ray diffraction (XRD), 29 Si magic angle spinning nuclear magnetic resonance ( 29 Si MAS NMR), Fourier transform infrared (FTIR) spectroscopy with pyridine, 2,6-di-tert-butylpyridine and CD 3 CN as probe molecules. Structural characteristics and acid-base properties of the zeolites depend on concentration of fluorine precursor in the reaction medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Kyriienko et al also reported a direct relationship between butadiene productivity and the relative amount of Lewis acid sites probed by CDCl 3 on Cu-doped Zr-containing zeolites. 26 Similar correlations have yet to be established on other materials, but there is strong evidence that Lewis acidity plays a role in other catalytic systems. 27 Another crucial component of catalysts active in the Lebedev process is their ability to convert ethanol to acetaldehyde.…”
Section: Introductionmentioning
confidence: 77%
“…Kyriienko et al also reported a direct relationship between butadiene productivity and the relative amount of Lewis acid sites probed by CDCl 3 on Cu-doped Zr-containing zeolites. 26 Similar correlations have yet to be established on other materials, but there is strong evidence that Lewis acidity plays a role in other catalytic systems. 27 Another crucial component of catalysts active in the Lebedev process is their ability to convert ethanol to acetaldehyde.…”
Section: Introductionmentioning
confidence: 77%
“…207 Tetrahedral hafnium, niobium and tantalum oxides sites are also known to form when dispersed on catalysts carriers, but can adopt different structures when in bulk. [219][220][221][222][223][224] Linear correlations between the acidity and catalytic activity with different catalysts were observed by other scholars: Kyriienko et al reported a correlation between the relative concentration of Lewis acid sites in Zr-MTW catalysts determined by FTIR spectroscopy of adsorbed CD 3 CN and butadiene productivity; 225 the present authors reported a direct correlation between the number of acid sites probed in Zn-Ta catalysts by NH 3 and the selectivity towards butadiene. 103 Contrarily, Dagle et al, who quantified the Lewis acid sites of Ag/ZrO 2 /SiO 2 catalysts with FTIR spectroscopy of pyridine, found that excessive Lewis acid site concentration caused by modifying the ZrO 2 loading lowered both butadiene selectivity and productivity in favor of ethanol dehydration products (Fig.…”
Section: Catalysis Science and Technologymentioning
confidence: 95%
“…Kyriienko et al prepared a hierarchical copper-doped Zr-MTW zeolite as a catalyst for the Lebedev process. 225 It was found that the nature and concentration of fluoride-containing mineralizing agents used during synthesis influenced the morphological characteristics, acid-base properties and catalytic activity in the Lebedev process. Better catalytic performances were obtained with HF and a Si : F ratio of 4, affording a butadiene selectivity of 68% and an ethanol conversion of 81% (Table 4, entry 22).…”
Section: View Article Onlinementioning
confidence: 99%
“…Recently, a number of well-ordered 2D and 3D supports have been investigated for the ETB process (Table 4). [29,98,[100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] Chae et al investigated the influence of the type of mesostructure, pore size and particle morphology of silicasupported Ta catalysts for BD production from ethanol and acetaldehyde. [100] The ordered mesoporous silicas (OMS), SBA-15 which has hexagonal pores in a 2D array with long 1D channels (pore diameters of 4.6-10.9 nm), KIT-6 with a bicontinuous cubic structure (pore diameter 7.9 nm) and MCM-41-type MMS with smaller 2D hexagonal pores (2.5 nm) were used as supports and loaded with 2 wt.% Ta.…”
Section: Structured Catalytic Systemsmentioning
confidence: 99%
“…For example, hierarchical Zr and Cu promoted MTW (ZSM-12; a high-silica zeolite with a 1-D pore system of straight channels formed from 12-membered rings) gave 55% BD yield at WHSV of 0.5 h À 1 . [109] Zeolite beta is used in a number of studies. This zeolite has a 3D pore system of intersecting channels formed by 12-membered rings and pore channels of 0.67 nm diameter.…”
Section: Structured Catalytic Systemsmentioning
confidence: 99%